Regional variation in states' naloxone accessibility laws in association with opioid overdose death rates-Observational study (STROBE compliant). Issue 22 (29th May 2020) - You, Hyo-Sun; Ha, Jane; Kang, Cyra-Y.; Kim, Leeseul; Kim, Jinah; Shen, Jay J.; Park, Seong-Min; Chun, Sung-Youn; Hwang, Jinwook; Yamashita, Takashi; Lee, Se Won; Dounis, Georgia; et al.
Abstract : Abstract: Though overall death from opioid overdose are increasing in the United States, the death rate in some states and population groups is stabilizing or even decreasing. Several states have enacted a Naloxone Accessibility Laws to increase naloxone availability as an opioid antidote. The extent to which these laws permit layperson distribution and possession varies. The aim of this study is to investigate differences in provisions of Naloxone Accessibility Laws by states mainly in the Northeast and West regions, and the impact of naloxone availability on the rates of drug overdose deaths. This cross-sectional study was based on the National Vital Statistics System multiple cause-of-death mortality files. The average changes in drug overdose death rates between 2013 and 2017 in relevant states of the Northeast and West regions were compared according to availability of naloxone to laypersons. Seven states in the Northeast region and 10 states in the Western region allowed layperson distribution of naloxone. Layperson possession of naloxone was allowed in 3 states each in the Northeast and the Western regions. The average drug overdose death rates increased in many states in the both regions regardless of legalization of layperson naloxone distribution. The average death rates of 3 states that legalized layperson possession in the West region decreased (-0.33 per 100, 000 person); however, in states in the West region that did not allow layperson possession and states in the Northeast region regardless of layperson possession increased between 2013 and 2017. The provision to legalize layperson possession of naloxone was associated with decreased average opioid overdose death rates in 3 states of the West region.